Biomolecular Corona Affects Controlled Release of Drug Payloads from Nanocarriers. (September 2020) - Sharifi, Shahriar; Caracciolo, Giulio; Mahmoudi, Morteza
Abstract : Nanomedicine has been widely used for a wide range of biomedical applications including drug delivery. Although many factors including the physicochemical properties of nanoparticles (NPs) and the payload efficacy of nanocarriers have been thoroughly investigated, the crucial role of the biomolecular corona in drug delivery and the release efficacy of nanocarriers demands further attention. This review highlights not only the crucial importance of the biomolecular corona to the drug release capacity of various types of nanocarriers, but also its interference with drug release measurements. A full consideration of the effects of the biomolecular corona on the controlled release and drug delivery of nanocarriers will help researchers design safer and more efficient nanobased drug delivery systems. Highlights: Nanoformulations have been extensively researched and used for their exciting potential to enhance the properties of conventional drugs and their ability for targeted delivery. Nanoformulations acquire a totally new 'biological identity' due to the formation of a biomolecular corona in vivo on contact with complex biological fluids. The formation of the biomolecular corona strongly influences the predictability of routinely conducted in vitro drug release kinetics studies, resulting in inaccurate results. A biomolecular corona forms not only on the systemic administration of nanoformulations into blood or plasma, as the release kinetics of a drug administered via oral and other parenteral routes such as inhalation will also be influenced by a biomolecular corona. Depending on the physicochemical properties of a nanocarrier or environmental parameters such as pH and temperature, the formation of the biomolecular corona can result in the attenuation or even acceleration of in vivo drug release kinetics. There is a strong need for the development of standard and validated in vitro release methods with the ability to measure release kinetics in the presence of a biomolecular corona.